ISAI: Investigating Solar Axion by Iron-57 - Tomonori Ikeda, Toshihiro Fujii, Takeshi Go Tsuru, Yuki Amano, Kazuho Kayama, Masamune Matsuda, Hiromu Iwasaki, Mizuki Uenomachi, Kentaro Miuchi, Yoshiyuki Onuki, Yoshizumi Inoue, Akimichi Taketa (SciPost Physics Proceedings, 2023)
The existence of the axion is a unique solution for the strong CP problem, and the axion is one of the most promising candidates of the dark matter. Investigating Solar Axion by Iron-57 (ISAI) is being prepared as a complemented table-top experiment to confirm the solar axion scenario. Probing an X-ray emission from the nuclear transitions associated with the axion-nucleon coupling is a leading approach. ISAI searches for the monochromatic 14.4 keV X-ray from the first excited state of $^{57}$Fe using a state-of-the-art pixelized silicon detector, dubbed XRPIX, under an extremely low-background environment. We highlight scientific objectives, experimental design and the latest status of ISAI.